Karen Fog Olwig: Cultural Adaptation and Resistance on St. John. Three Centuries of Afro-Caribbean Life. (University of Florida Press, 1985). XII+227 s.,20. - Gøbel, Erik (Historie/Jyske Samlinger, 1991)
-